2020
DOI: 10.1186/s41938-020-00288-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold storage temperature on quality of the parasitoid, Trichogrammatoidea bactrae Nagaraja (Hymenoptera: Trichogrammatidae)

Abstract: This study was designed to find out the optimum cold storage temperature (4, 7, and 10 °C) and storage period (1–16 weeks) of 3 different immature developmental stages (2, 4, 6 days post parasitism) of the egg parasitoid, Trichogrammatoidea bactrae Nagaraja (Hymenoptera: Trichogrammatidae) to produce high-quality individuals to be utilized. Also, the effects of cold storage on parasitoids’ fitness in terms of parasitism percentage, developmental period, adults’ emergence percentage, female percentage, and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…This may be because of the cold temperatures, which decrease the quality and vitality of parasitized eggs. Our results were in harmony with the findings of El Khayat et al, 2001 , Farid et al, 2001 , Chen et al, 2008 , Mohamed and El-Heneidy, 2020 they found that the adult female’s percentages were significantly influenced by the cold storage durations. In comparison with the non-cold-stored parasitized eggs, the female’s percentage declined by 4.01, 8.22, 13.26, 18.60, 25.14, 25.43, 28.13, 28.20, 29.97, and 30.94% in cold storage parasitized eggs for 3, 6, 9, 12, 15, 18, 21, 24, 27, and 30 days, respectively ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This may be because of the cold temperatures, which decrease the quality and vitality of parasitized eggs. Our results were in harmony with the findings of El Khayat et al, 2001 , Farid et al, 2001 , Chen et al, 2008 , Mohamed and El-Heneidy, 2020 they found that the adult female’s percentages were significantly influenced by the cold storage durations. In comparison with the non-cold-stored parasitized eggs, the female’s percentage declined by 4.01, 8.22, 13.26, 18.60, 25.14, 25.43, 28.13, 28.20, 29.97, and 30.94% in cold storage parasitized eggs for 3, 6, 9, 12, 15, 18, 21, 24, 27, and 30 days, respectively ( Table 2 ).…”
Section: Resultssupporting
confidence: 92%
“…Also, cold storage durations had a clear negative impact on the emergence rate with T. nerudai ( Tezze and Botto, 2004 ), and T. cordubensis ( Ventura Garcia et al, 2002 ). The reduction in the percentage of adult females increased by extended cold storage times ( El Khayat et al, 2001 , Mohamed and El-Heneidy, 2020 ). Moreover, the longevity of adult females of T. evanescence decreased as the storage durations extended at 4 °C ( Karabörklü and Ayvaz, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, adverse effects occurred with egg hatching of H. axyridis following long‐term cold storage, although the egg production of the F 1 offspring remained unaffected 40 . When exposed to lower temperatures, the mortality of Trichogrammatoidea bactrae (Nagaraja) (Hymenoptera: Trichogrammatidae) larvae escalated significantly, and these detrimental effects were inherited 41 . DNA methylation may act as a pivotal mechanism that transmits the consequences of chilling damage from the maternal generation to the F 1 generation 42 …”
Section: Discussionmentioning
confidence: 99%
“…40 When exposed to lower temperatures, the mortality of Trichogrammatoidea bactrae (Nagaraja) (Hymenoptera: Trichogrammatidae) larvae escalated significantly, and these detrimental effects were inherited. 41 DNA methylation may act as a pivotal mechanism that transmits the consequences of chilling damage from the maternal generation to the F 1 generation. 42 In conclusion, our study suggests that Anisopteromalus calandrae can be successfully maintained in long-term cold storage at 13 °C for up to 90 days without considerable undesirable effects on their suitability.…”
Section: Discussionmentioning
confidence: 99%
“…Storage time plays a key role in the production of Anastatus species, in that a longer storage time can provide a flexible supply of parasitoids for their timely and urgent field release in biological control programmes. The most commonly used preservation method for an egg parasitoid is cold storage (45)(46)(47)(48). However, this method not only fails to guarantee its shelf life but also affects the quality of natural enemy products (23,49,50).…”
Section: Transgenerational Photoperiod Effects Have Been Shown To Inf...mentioning
confidence: 99%